Circulação da fé na mídia social: crenças em reelaboração - Oliveira, Frederico Ramos (2015)
Nowadays, social media has become an important social space in which emerges new communities. Religiousness participates in these communities while is transformed by these social media’s economy. By content analysis of ten videos from vlogs, and their comments, it appoints that there are some specific dynamics to legitimate someone on YouTube. Religious content contributes sharing legitimacy to its preachers, as the religious vlogger. However, it also rely on other elements as how one presented his own argument, if it is similar to user’s ideas, and the way a vlogger looks. A vlog is a YouTube gender and spread a debate about a theme, but also can be record after a community call. It offers specific conditions for a qualified discussion when the youtubers agree to obey the community ethic. In the social media, the religious content is publicized, discussed and is elaborated again. An act of reflection about social facts creates some ethic ideals. They change what is considered forbidden and how this notion is conceived and how it is questioned. This are some aspects of religious meaning circulation in YouTube.